2021
DOI: 10.1080/10408444.2021.1944056
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of animal studies in the toxicological assessment of oil and wax hydrocarbons. Solving the puzzle for a new outlook in risk assessment

Abstract: Paraffin waxes and white mineral oils are distinct petroleum products separated from a common feedstock by crystallization, where only n-alkanes, iso-and cyclo-alkanes with a linear backbone of $ 20 carbon atoms long, selectively crystalize out from the oil to form the wax, which is solid at room temperature, whereas oils remain liquid. Up until the 90's, these differences were reflected in separated regulatory assessments. A paradigm shift occurred when Fischer 344 rats (F-344) developed liver epithelioid gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 66 publications
(208 reference statements)
0
20
0
Order By: Relevance
“…The authors concluded that this was consistent with a lack of evidence for formation of epithelioid granulomas in humans. This conclusion is supported by a proposed adverse outcome pathway (AOP) analysis (Carrillo et al., 2021a,b). In humans, liver lesions consisted of accumulation of saturated hydrocarbons and lipoid granulomas of no clinical relevance.…”
Section: Assessmentmentioning
confidence: 79%
“…The authors concluded that this was consistent with a lack of evidence for formation of epithelioid granulomas in humans. This conclusion is supported by a proposed adverse outcome pathway (AOP) analysis (Carrillo et al., 2021a,b). In humans, liver lesions consisted of accumulation of saturated hydrocarbons and lipoid granulomas of no clinical relevance.…”
Section: Assessmentmentioning
confidence: 79%
“…However, Carrillo et al. ( 2021 ) considered Wax 4 (Section 3.1.1 ) to be representative of one of the paraffin waxes tested in Shubik et al. (1962), based on the same overall physical properties, the chain length range and the content of n ‐, mono‐branched and monocyclic alkylated cycloalkanes.…”
Section: Assessmentmentioning
confidence: 99%
“…However, it was not demonstrated that the metabolism ended with complete degradation. Recently, Carrillo et al (2021) proposed a mode of action analysis within an Adverse Outcome Pathway framework to better explain how the decreased metabolism, leading to an accumulation of n-alkanes in the Fischer 344 liver, were the key events triggering the production of wax crystals with the epithelioid granuloma formation (possibly triggering inflammation). The accumulation in humans, mainly in adipose tissue, does not reflect the accumulation in rats, especially the Fischer 344 strain, mainly due to the time course difference in hepatic clearance (Barp et al, 2017;Cravedi et al, 2017).…”
Section: Toxicokinetics 14mentioning
confidence: 99%
See 1 more Smart Citation
“…The type and quantity of aromatic constituents in petroleum substances vary depending on the source of the crude oil feedstock and the processing conditions applied during their manufacturing process (Mackerer et al 2003 ; Tsitou et al 2015 ; Carrillo et al 2022 ). For example, aromatic extracts, obtained upon solvent extraction of distillates or the residue from a vacuum tower, contain a relatively high concentration of dimethyl sulfoxide (DMSO)-extractable aromatics (6.6–20.3%, mostly 3- to 7-ring PACs) (HPV 2012 ; Carrillo et al 2021 ). Whereas, highly refined petroleum products, such as highly refined base oil (HRBO) and petroleum derived-waxes, obtained upon dewaxing, deoiling and/or hydrotreatment of base oil process, contain mainly highly alkylated 1- to 2-ring aromatics because the hazardous 3- to 7-ring aromatic compounds in these products are removed during the refinement (Fig.…”
Section: Introductionmentioning
confidence: 99%